1992
DOI: 10.1002/chin.199234317
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: The Mechanism and Application of Fungal Biosorption to Colour Removal from Raw Waters.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…A number of studies (Akar et al, , 2008Bakshi et al, 2006;Banks and Parkinson, 1992;Chu and Chen, 2002a,b;Fu and Viraraghavan, 2002a,b, 2000Khalaf, 2008;Low et al, 1995;Tunali et al, 2007) has been carried out to investigate the efficiencies and mechanism of the removal of dyes by various types of biomass, and some review on biosorption (Aksu, 2005) too exists. Biomass of non-living dried roots of water hyacinth (without any pretreatment) was explored by Low et al (1995) as an adsorbent for the removal of methylene blue and victoria blue and the authors found that it possessed good adsorptive capacity of 128.9 and 145.4 mg g À1 , for methylene blue and victoria blue, respectively.…”
Section: Low-cost Alternative Adsorbentsmentioning
confidence: 99%
“…A number of studies (Akar et al, , 2008Bakshi et al, 2006;Banks and Parkinson, 1992;Chu and Chen, 2002a,b;Fu and Viraraghavan, 2002a,b, 2000Khalaf, 2008;Low et al, 1995;Tunali et al, 2007) has been carried out to investigate the efficiencies and mechanism of the removal of dyes by various types of biomass, and some review on biosorption (Aksu, 2005) too exists. Biomass of non-living dried roots of water hyacinth (without any pretreatment) was explored by Low et al (1995) as an adsorbent for the removal of methylene blue and victoria blue and the authors found that it possessed good adsorptive capacity of 128.9 and 145.4 mg g À1 , for methylene blue and victoria blue, respectively.…”
Section: Low-cost Alternative Adsorbentsmentioning
confidence: 99%
“…aerobic granules and metal species in aqueous solution, are in contact, they are surrounded by an electrical double layer as a result of electrostatic interaction. 30,31 The total interaction forces decrease as the double-layer repulsion forces decrease, since the double layer becomes compressed at high IS, while the van der Waals attraction forces remain independent of the solution IS. 32,33 On the other hand, the higher biosorption capacity at high IS is possibly due to the compression of the double layer resulting in a closer approach of Cu(II) ions and aerobic granules, which increases the biosorption capacity of the biomass.…”
Section: Effect Of Ph and Is On Cu(ii) Biosorptionmentioning
confidence: 98%
“…As a result, each FA molecule occupies less surface area resulting in a higher sorption density [29,37]. In addition, the colloidal chemistry theory [38] and the Derjaugin, Landau, Verwey, and Overbeek (DLVO) theory [39] indicated that at low ionic strength, FA has extended electric double layers, but as described by the DLVO theory, the double layer becomes compressed at high ionic strength, reducing the surface potential, but keeping the surface charge density constant. The compression of Scheme 2.…”
Section: Effect Of Ionic Strengthmentioning
confidence: 99%